2001
DOI: 10.1054/bjoc.2000.1669
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-interferon does not increase the efficacy of 5-fluorouracil in advanced colorectal cancer

Abstract: Two meta-analyses were conducted to quantify the benefit of combining α-IFN to 5FU in advanced colorectal cancer in terms of tumour response and survival. Analyses were based on a total of 3254 individual patient data provided by principal investigators of each trial. The meta-analysis of 5FU ± LV vs. 5FU ± LV + α-IFN combined 12 trials and 1766 patients. The meta-analysis failed to show any statistically significant difference between the two treatment groups in terms of tumour response or survival. Overall t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…IFNα could potentiate 5-FU activity for CRC treatment by enhancing activities of effector cell or modulating display of HLA class I antigens [ 118 ]. Meta-analysis of data from multiple trials concluded however that IFNα did not increase the efficacy of 5-FU or 5-FU+LV and that 5-FU+IFNα was significantly inferior to 5-FU+LV [ 9 ]. The type II IFN IFNγ was also evaluated for enhancing 5-FU’s anti-tumor activity.…”
Section: Modulation Of 5-fu-induced Anti-tumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…IFNα could potentiate 5-FU activity for CRC treatment by enhancing activities of effector cell or modulating display of HLA class I antigens [ 118 ]. Meta-analysis of data from multiple trials concluded however that IFNα did not increase the efficacy of 5-FU or 5-FU+LV and that 5-FU+IFNα was significantly inferior to 5-FU+LV [ 9 ]. The type II IFN IFNγ was also evaluated for enhancing 5-FU’s anti-tumor activity.…”
Section: Modulation Of 5-fu-induced Anti-tumor Immunitymentioning
confidence: 99%
“…Both type I and II interferons also were evaluated in combination with 5-FU and strong efficacy was found in some clinical studies consistent with their immunomodulatory properties [ 8 ]. Ultimately, immunomodulatory approaches to enhancing 5-FU efficacy were shown to be inferior to biochemical modulation with leucovorin (LV) [ 9 ], a reduced folate [ 10 ] that promotes thymidylate synthase (TS) inhibition by 5-FU [ 11 ]. TS is essential for de novo pyrimidine biosynthesis and its inhibition causes malignant cells to undergo “thymineless death” [ 12 ], a well-validated strategy for cancer treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interferon-α does not enhance activity of 5-fluorouracil (5-FU) in colon cancer (Hill et al, 1995 ; Thirion et al, 2001 ). Interferon-α plus retinoid adds no benefit to pulsed cisplatin in cervical cancer (Basu et al, 2016 ).…”
Section: Master Modulators the Backbone Of Anakoinosis Inducing Thermentioning
confidence: 99%
“…Apart from the critical role in modulating immune responses [ 38 ], Type I IFN is also known to have a direct effect on cancer cells [ 39 ] and can potentiate 5FU cytotoxicity by inducing S-phase accumulation and apoptosis [ 40 43 ]. In clinical studies, recombinant IFNs in combination with 5FU have been shown to be effective in some [ 44 47 ], but not in others [ 48 , 49 ]. Significant challenges limiting the clinical benefits include the issues of systemic toxicities and short half-life of recombinant IFNb [ 41 , 50 ].…”
Section: Introductionmentioning
confidence: 99%